Archaeological salvage projects 1972 - Byrne, William J., 1945- (Mercury series., 1974)
Reports on 20 of the 25 archaeological salvage projects carried out in 1972. Included are investigations made in the Aishihik drainage system, Button Point, NWT and Cumberland Sound.